Letter from Maurice Walsh to Lily O'Brennan concerning a forward for her book, - Walsh, Maurice, 1879-1964 (1942)
Walsh has written a forward to O'Brennan's new book for children; he writes "I kept it short as I could, for personally, I abhor long forwards [...] You will forgive me if the foreword is inadequate, and you will put it in the fire - I mean the waste-paper bag - and say commisseratingly 'Poor Walsh, he's done'". Also included is the forward, praising the story and central characters.